Content Analysis of 4 Fear of Falling Rating Scales by Linking to the International Classification of Functioning, Disability and Health. Issue 7 (1st March 2013) - Bladh, Stina; Nilsson, Maria H.; Carlsson, Gunilla; Lexell, Jan
Abstract : Objective: To gain a deeper understanding of the content of 4 fear of falling (FOF) rating scales by linking them to the International Classification of Functioning, Disability and Health (ICF). Design: Linking study according to the ICF linking rules. Setting: Not applicable. Patients: Not applicable. Methods: The rating scales were the Falls Efficacy Scale–International (FES‐I), the Swedish version of the Falls Efficacy Scale (FES[S]), the Activities‐specific Balance Confidence Scale (ABC), and the modified Survey of Activities and Fear of Falling in the Elderly (SAFFE). The process followed the established and updated linking rules. Three linkers independently identified all meaningful concepts in the rating scales and linked them to the most precise ICF categories. The linkers then discussed their results to reach consensus. If consensus was not attained, the linkers pursued the discussions with a fourth person to reach consensus. Main outcome measurements: Not applicable. Results: Most meaningful concepts from the overall questions were linked to the ICF component of body functions. Of the 62 items, all but one meaningful concept were linked to the component of activities and participation. All 4 rating scales covered the chapters of mobility and domestic life and had most linkages to the mobility chapter. Conclusions: The linking process revealed similarities and differences between the 4 FOF rating scales, as well as methodologic challenges in linking instruments to the ICF. By providing a content description that allows for a direct comparison of the rating scales, the results may be helpful when choosing an appropriate rating scale assessing FOF in clinical practice and research. A further head‐to‐head comparison through psychometric analyses is required to recommend appropriate FOF rating scales. Studies are also needed to investigate how the overall question and response categories of a rating scale affect respondents' answers.